Stolen trauma: why some veterans elaborate their psychological experience of military service. Issue 1 (2nd January 2016) - Jones, Edgar; Milroy, Hugh
ABSTRACT: The embellishment of a warrior biography has a long history but examples of veteran elaboration of traumatic experience have become increasingly apparent. Although legislative change in the UK has removed the penalties for fabrication and a progressive decline in the military footprint may have increased the likelihood of such false trauma narratives, a paradigm shift in explanations for mental illness underpins this phenomenon. The recognition of post-traumatic stress disorder (PTSD) in 1980, followed by studies to identify risk factors, led to a greater appreciation of psychological vulnerability. As a result, the use of shame to discourage acts formerly labelled as "cowardly" or "lacking in morale fibre" is no longer considered appropriate. Recent conflicts in Iraq and Afghanistan generated popular sympathy for service personnel, whilst media focus on PTSD has led the UK public to believe that most veterans have been traumatised by their tours of duty.